Analysis of Local Wisdom "Siri" in Leadership Of The Head of Temmappadaue Village, Marusu District, Maros Regency - Aras Solong; Tetty Dwiyanti; Muh Alwi; Ashariana Ashariana (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study aims to determine the value of local wisdom leadership "siri" as a motivational tool to improve the implementation of tasks and work of employees at the Temmappaduae Village office. Study This use A qualitative approach with data collection techniques through observation of research objects, direct interviews with informants and documentation, namely tracing evidence in the form of written decisions and regulations, books or magazines. The data analysis techniques used are data collection techniques, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the leadership value of local wisdom "siri" as a basis in providing encouragement to carry out employee encouragement and work by using indicators alempureng (honesty), amaccang (education), assitinajang ( appropriateness ), agettengeng (firmness) and reso (effort) which must be held and upheld firmly by an employee accompanied by a high commitment in carrying out the tasks and work that are his responsibility. The results of the study found that the leadership value of local wisdom "Siri" if implemented well will produce good and responsible performance. Furthermore, things that are considered to affect the implementation of employee tasks and work that are not optimal can be eliminated if leadership value factors such as warani (brave), masagena (ability) and makaritutu (vigilance) in supporting efforts to improve performance must be held firmly and become a driver for employees in carrying out tasks and work to support maximum employee performance.Leadership